Pengaruh Faktor Makroekonomi terhadap Profitabilitas BUS: Studi pada Bank Umum Syariah di Indonesia yang Terdaftar Dalam OJK Periode 2018-2020 - Emylia Dwi Maharani; Ahmad Budiman (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The purpose of this study is to determine the impact of inflation, exchange rates, and Gross Domestic Product (GDP) on the profitability of Islamic banking which in this study uses the ratio of Return on Assets (ROA) and Return on Equity (ROE). The object of research is 11 Islamic Commercial Banks that publish their financial reports to the Otoritas Jasa Keuangan for the period 2018-2020. The data used include quarterly statistics compiled from the websites of Bank Indonesia, the Badan Pusat Statistik, and Otoritas Jasa Keuangan from 2018 to 2020. The research was conducted using a quantitative methodology. After testing, it was found that inflation, exchange rate, and GDP simultaneously did not have a significant effect on ROA and ROE. Partially the exchange rate and GDP have a significant impact on ROA and ROE, but inflation does not. Keywords: Inflation, Exchange Rate, GDP, ROA, ROE